Analisis Beban Kerja dan Motivasi Kerja Guru Produktif Dalam Pengelolaan Teaching Factory (TeFa) Di Sekolah Menengah Kejuruan (SMK) - Matilda Indriani Umbu Warata; Lisa G Kailola; Hotmaulina Sihotang (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The implementation of Teaching Factory (TeFa) in vocational high schools is intended to strengthen the link between school-based learning and the demands of the industrial world. However, this model also changes the work structure of productive teachers because they are required to act not only as educators, but also as production supervisors, quality controllers, and coordinators of school-industry activities. This study aims to analyze the forms of workload experienced by productive teachers and to synthesize the factors that influence their work motivation in TeFa management. This research used a descriptive qualitative approach with a literature review method. The reviewed sources consisted of journal articles, books, policy documents, and previous studies published between 2015 and 2025, selected based on their relevance to TeFa, teacher workload, work motivation, and vocational education management. Data were analyzed through content analysis and thematic synthesis. The findings show that productive teachers experience physical, cognitive, emotional, and organizational workloads. These workloads may support performance when they are managed fairly, but may reduce motivation and increase the risk of burnout when they are not accompanied by clear task distribution, block scheduling, managerial support, and a proportional reward system. This study contributes a conceptual balance model between workload management and teacher motivation as a basis for strengthening sustainable TeFa governance in vocational schools.